THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR SHARE (TPS) TO INCREASE THE COGNITIVE AND AFFECTIVE LEARNING OUTCOMES OF THE STUDENTS IN ART IN YEAR VIII-A STUDENTS OF MTsN 3 WEST ACEH, ACADEMIC YEAR 2021/2022 - Arifin, Jainul (LUMBUNG AKSARA, 2022)
This study aims to determine and analyze the improvement of students' affective and cognitive learning outcomes of MTsN 3 West Aceh in Art through the implementation of the Think Pair Share (TPS) cooperative learning model. This research was a Classroom Action Research (CAR). The sample of this research was Year VIII-A students with the total number of students was 31 students. The data collection techniques used were observation, interviews, documentation, and tests. The results showed that the implementation of the Think Pair Share cooperative learning model improved students' affective learning outcomes for discipline, responsibility, mutual respect, curiosity, and confidence in learning. In terms of cognitive learning outcomes, the innovation of the learning model was able to create effective and fun learning, develop critical thinking skills in solving problems and improve students’ test results that made students’ learning outcome optimal. Based on the research observations, the students’ affective learning outcomes have increased after the implementation of the Think Pair Share cooperative learning model with an average pre-action percentage of 63%, and 92% after the action. Based on the pretest and the posttest of the study, the students' cognitive learning outcomes also increased with an average percentage of pre-action by 43.39% and increased into 97% after the implementation of the learning model. The statistical calculations showed that there was a significant difference in the average value of students' affective and cognitive learning outcomes in the pretest (before the action) and the posttest (after the action).